High-performance dual-mode self-calibrating optical thermometry for Er3+, Li+ co-doped oxides. Issue 47 (21st November 2022) - Jiang, Hongming; Jia, Hong; Zhang, Yuping; Zhang, Xian; Feng, Zhenyi; Yuan, Yuquan; Chen, Zhi; Hu, Yanfei; Peng, Feng; Liu, Xiaofeng; Qiu, Jianrong
Abstract : A dual-mode self-calibrating temperature measurement strategy was proposed, by leveraging the temperature-dependent ratios of UC emission intensities from the thermally-coupled and non-thermally coupled energy levels of Er 3+ ions. Abstract : Temperature measurement based on thermally dependent emissions from intra-configurational 4f–4f transitions of rare earth ions has been developed as an efficient method for non-contact thermometry, but it remains challenging for high resolution temperature measurement due to the inherent limitation of the energy gap (200–2000 cm −1 ) between the thermally coupled energy levels (TCELs). In this work, a group of oxide phosphors, Y2 O3 : x Er 3+, y Li +, prepared by a low-temperature combustion method (LCM) were developed for dual-mode optical thermometry by leveraging the temperature-responsive upconversion (UC) emission from Er 3+ ions. We discover that the introduction of the dopant (Li + ion) into Y2 O3 : Er 3+ synthesized by the LCM can significantly regulate the original crystal configuration and its surface structure. Its transition to a monocrystalline state can solve the problem of high impurity defects and possible high dislocation density that cannot be overcome by a polycrystalline state, thus remarkably increasing the emission intensity of UC (about 28 times). In addition, the dual-mode optical thermometry based on thermally coupled energy levels (TCELs) and non-thermally coupled energy levels (NTCELs) was examined with respect to the different temperature dependence of the three characteristic emission peaks of the Er 3+ ions ( i.e., from excited levels of 2 H11/2, 4 S3/2 and 4 F9/2 ). At temperatures from 123 to 443 K, the maximum relative sensitivities ( S Rmax ) are 6.67% K −1 and 1.13% K −1 and the maximum absolute sensitivity ( S Amax ) reaches 0.42% K −1 and 2.48% K −1, respectively. The excellent sensitivity at low temperatures indicates that our results not only provide an effective doping strategy for improving the crystal type character and surface structure of oxide phosphors, but also provide an effective guideline for the low temperature environmental applications of functional upconversion optical thermometers.